Transphobia and Cisgender Privilege: Pre-Service Teachers Recognizing and Challenging Gender Rigidity in Schools - Kearns, Laura-Lee; Mitton-Kukner, Jennifer; Tompkins, Joanne (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
Our study provides examples of how critical curricula and social justice education can be brought together to inform teacher education. Building upon our ongoing longitudinal study, which investigates the impact of an integrated LGBTQ awareness program, we focus in this article on five pre-service teachers who identified critical incidents in schools related to transphobia and gender construction, and who were concerned about the enduring gender binary that presents itself in schools. Their experiences highlight the ways in which gender surveillance, both overtly and covertly, reinscribes heteronormativity, and that homophobia, transphobia, and gender stereotypes need to be continuously challenged.